Photos found in the archive. An approximation to the work with images based on an amateur album about children’s games (Argentina, end of the 19th century - Dussel, Inés (Historia y Memoria de la Educación, 2019)
This article presents a study of a series of photos on children’s games that is preserved at the National General Archive in Argentina as part of the Fond of the Argentinean Photographic Society of Amateurs, active between 1889 and 1925. The album contains 77 pictures of unusual quality that present heterogeneous groups of children playing diverse games in different settings. The photos include little information about how they were produced, but a detailed research and analysis can reveal different aspects of the production of images of childhood at that time. The text presents, in its first part, some general considerations about photography as historical documents and its truth-claims; in the second part, it discusses the social biography of these images, looking at the available information in its peri-textual inscriptions to trace its conditions of production, authorship, and circulation, and introduces the analysis of some of its contents, particularly in relation to how these images, in their aesthetic choices, collaborate in the production of a new iconography of childhood. The final section raises some reflections about the ethical demands of working with photographs, calling for an in-depth study that makes room for their singularization and contributes to redefining the politics of the archive and of memory in the history of education.